2019
DOI: 10.3889/oamjms.2019.678
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Dental Interns to Treat Pregnant Patients

Abstract: BACKGROUND: Pregnancy causes major changes in maternal physiology and metabolism, which may lead to increased susceptibility to oral infection. AIM: Aim of this study is to assess the awareness of dental interns regarding the management of the dental needs of pregnant patients. METHODS: A cross-sectional questionnaire survey was conducted among 188 interns of a private dental college in Saudi Arabia. The questionnaire comprised of 14 knowledge-based questions regarding their training, awareness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 15 publications
11
11
0
1
Order By: Relevance
“…Our study indicated that dental interns and dentists have fair levels of knowledge that need improvement. This is similar to previous studies in Nigeria [11] and Saudi Arabia [23], but different from others in India [25], Australia [22], and Saudi Arabia [28]. It should be noted that this difference might be due to different levels of education between cities and countries and the type of continuous education participants receives.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our study indicated that dental interns and dentists have fair levels of knowledge that need improvement. This is similar to previous studies in Nigeria [11] and Saudi Arabia [23], but different from others in India [25], Australia [22], and Saudi Arabia [28]. It should be noted that this difference might be due to different levels of education between cities and countries and the type of continuous education participants receives.…”
Section: Discussionsupporting
confidence: 84%
“…The majority of participants in our study acknowledged the importance of providing endodontic treatment and pain relief for pregnant patients, which was similar to responses in a previous study [11]. The majority of the study participants knew that pregnant patients require special positioning, which was similar to a prior study in Nigeria, but higher than a previous local Saudi Arabian study (27%) [28]. The reason for this is likely that the prior Saudi study was specifically assessing the dentist's knowledge about a semi-reclined position with a pillow under the patient's right side [28].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The literature states that up to 43% of pregnant women may suffer from pathologies of odontogenic origin that can be dangerous for both the pregnant woman and the fetus because they can rapidly progress to systemic infections [39][40][41], and they should be treated aggressively to avoid further complications [41]. If drainage of the infection is not possible or there is severe inflammation or systemic involvement such as fever, antimicrobial treatment should be chosen [39], always weighing the risk and benefit to the mother and fetus [39,40,42,43], regardless of the trimester of gestation [44]. However, there is a consensus that antibiotic prescription during the first trimester of pregnancy should be avoided where possible, as it is linked to iatrogenic teratogenicity [38].…”
Section: Discussionmentioning
confidence: 99%